2018
DOI: 10.1101/469619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scleraxis Lineage Cells Contribute to Organized Bridging Tissue During Tendon Healing, and Identifies Subpopulations of Resident Tendon Cells

Abstract: During tendon healing, it is postulated that intrinsic tendon cells drive tissue regeneration while extrinsic cells drive pathological scar formation. Intrinsic tendon cells are frequently described as a homogenous, fibroblast population that is positive for the marker Scleraxis. It is controversial whether intrinsic Scleraxis localize within the forming scar tissue during adult tendon healing.We have previously demonstrated that calcium binding protein S100a4 is a driver of tendon scar formation and marks a s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A similar proliferative response is seen in the endotenon in an equine collagenase-induced flexor tendon injury model, however the identity of these cells and how they contribute to the healing response has yet to be determined (92). During both murine flexor and patellar tendon healing, cells derived from the epitenon/paratenon appear to migrate into the injury area (29,95). Taylor et al demonstrated that the murine tendon epitenon is positive for the basal lamina-related protein laminin during homeostasis (44), and Gelberman et al found that epitenon cells express elevated levels of fibronectin compared to the tendon body shortly following injury (94).…”
Section: Fibroblastic/proliferative Phasementioning
confidence: 92%
See 4 more Smart Citations
“…A similar proliferative response is seen in the endotenon in an equine collagenase-induced flexor tendon injury model, however the identity of these cells and how they contribute to the healing response has yet to be determined (92). During both murine flexor and patellar tendon healing, cells derived from the epitenon/paratenon appear to migrate into the injury area (29,95). Taylor et al demonstrated that the murine tendon epitenon is positive for the basal lamina-related protein laminin during homeostasis (44), and Gelberman et al found that epitenon cells express elevated levels of fibronectin compared to the tendon body shortly following injury (94).…”
Section: Fibroblastic/proliferative Phasementioning
confidence: 92%
“…Chemotactic signaling from a number of important growth factors, including TGF-β family members (28), platelet-derived growth factor BB (PDGF-BB) (90, 91), insulin-like growth factor-1 (IGF-1) (92), and basic fibroblast growth factor (bFGF) (93) are thought to stimulate the proliferation and migration of various fibroblast populations, with the majority of the early healing response appearing to originate from cells derived from the epitenon and not from the tendon body itself. Shortly following injury, epitenon cells adjacent to the injury site begin to proliferate and form a thickened epitenon layer in both canine and murine models (29,94,95). A similar proliferative response is seen in the endotenon in an equine collagenase-induced flexor tendon injury model, however the identity of these cells and how they contribute to the healing response has yet to be determined (92).…”
Section: Fibroblastic/proliferative Phasementioning
confidence: 99%
See 3 more Smart Citations